Novel cost-effective and portable three-dimensional force measurement system for biomechanical analysis: a reliability and validity study - Hao, L.; Yin, C.; Duan, X.; Wang, Z.; Zhang, M. (Sensors, 2024)
The application of dynamic data in biomechanics is crucial; traditional laboratory-level force measurement systems are precise, but they are costly and limited to fixed environments. To address these limitations, empirical evidence supports the widespread adoption of portable force-measuring platforms, with recommendations for their ongoing development and enhancement. Taiyuan University of Technology has collaborated with KunWei Sports Technology Co., Ltd. to develop a portable 3D force measurement system. To validate the reliability of this equipment, 15 male collegiate students were randomly selected to perform four distinct movements: walking, running, CMJ, and side-cutting. The Bertec system served as a reference device alongside the KunWei system to collect the kinetic characteristics of the test movements. The consistency and fitting quality between the two devices were evaluated through t-tests, ICC, and NRMSE. The research results indicated that there were no significant differences in peak force between the KunWei system and the Bertec system across all four movements (p > 0.05). The ICC values for force-time curves were all above 0.98, with NRMSE not exceeding 0.165. The KunWei system exhibited high consistency and reliability under various motion conditions compared to the Bertec system. This system maintains data accuracy, significantly broadens the application scope of force measurement systems, and reduces procurement and maintenance costs. It has been successfully applied in technical support for multiple water sports and winter projects with ideal results achieved.